„Z” generáció fő jellemzői és a várható munkerő-piaci kihívások = Main characteristics of generation Z and the challenges to come in the labour market - Ruzsa, Roland Csaba (Közép-Európai Közlemények, 2018)
The generation Z is a new generation that can described as the first digital generation. Based on our survey, the Z generation uses the internet as daily platform for communication, social interactions and even for shopping. This generation is open to receive almost everything through the internet, however, it has to come fast. The smart phone is their most valuable tool to step into the virtual community. They use platforms that were not even known ten years ago. They tend to express their feelings, emotions and thoughts in a very fast way using apps. This app use behaviour may lead to new changes in their attitude to the education system and later on, even to the work they want to pursue. The labour market will have to face up to new challenges and demands of this generation regarding flexibility, digital work environment. They also wish to follow their dreams in their work. I summarize below the main attributes of generation Z members and identify the possible challenges that their appearance may trigger in the labour market.